1969
DOI: 10.1084/jem.129.6.1183
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response

Abstract: The ability of 7S and F(ab')2 antibody fragments to suppress priming with low doses of antigen was compared. The 7S preparation was approximately 100–1000 times more potent than the F(ab')2 preparation when the agglutinin titers of the two preparations were the same. The presence of any ability to suppress priming in the F(ab')2 preparation may reflect an inherent capacity of the F(ab')2 antibody or contamination with small amounts of 7S antibody. The difference between 7S and F(ab')2 antibody i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…A detailed analysis of the cellular mechanism of antibody-mediated immune suppression is the subject of a forthcoming communication. Studies of suppression of the immune response by antibody fragments in vivo have yielded conflicting results (26,(32)(33)(34), partly due to the increased catabolism of these fragments (35). The effect of antibody fragments on the immune response in vitro, without the drawback of increased catabolism, should be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of the cellular mechanism of antibody-mediated immune suppression is the subject of a forthcoming communication. Studies of suppression of the immune response by antibody fragments in vivo have yielded conflicting results (26,(32)(33)(34), partly due to the increased catabolism of these fragments (35). The effect of antibody fragments on the immune response in vitro, without the drawback of increased catabolism, should be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…19,[41][42][43] In addition, the inhibitory potential of an antibody is markedly reduced if its interaction with Fc␥RIIB is abolished by deglycosylation. 44 However, inhibition through Fc␥RIIB has been dismissed as a possible mechanism based on 3 observations: an IgG3 isotype antibody, which in the mouse does not bind to Fc␥RIIB, can be inhibitory 18,19 ; in some studies, F(abЈ) 2 fragments can also inhibit B-cell responses 17,20,21 ; and IgG is inhibitory in Fc-receptor knockout mice.…”
Section: Mechanism Of Maternal Antibodies 6147mentioning
confidence: 99%
“…A number of laboratories have demonstrated that the removal of the oligosaccharide chain from the IgG molecule affects several Fc effector functions, especially the ability to bind to Fc receptors (FcR) [14][15][16]. Although there are a number of factors that affect the clearance of IgG (either monomeric, or as part of an immune complex), the ability to bind to FcRs expressed on a number of different cell types influences not only the degradation of the molecule [17], but, in some cases, even the subsequent synthesis [18]. In general, the high-affinity FcRI appears to be important for binding monomeric IgG, whereas immune complexes, containing IgG, interact with FcRII and FcRIII [19].…”
Section: Introductionmentioning
confidence: 99%